INFLUENCE OF DIFFERENT CHEMICAL AGENTS AND STORAGE CONDITIONS ON THE MICROBIOLOGICAL CONTENT OF INDUSTRIAL HEMP (Cannabis sativa L.) SEEDS - Đerić, Nataša (Food and Feed Research, 2020)
The aim of this study was to test different chemical agents to obtain microbiologically safe industrial hemp seeds that could be used for further food processing (with the reduced total number of microorganisms, total number of yeasts and moulds, and total number of Enterobacteriaceae). In order to obtain seeds applicable for food consumption, optimal storage temperature conditions (room temperature, refrigerator, freezer), method of seed packaging (vacuum / without vacuum), and the application of various chemical treatments (ethanol, sodium hydrogen carbonate, sodium hypochlorite) were tested on the certified industrial hemp seeds, produced in two consecutive years. Optimal storage conditions differed for different microorganisms, and the most optimal storage was at room temperature, for seeds produced in 2018, and in treatment to reduce the number of Enterobacteriaceae and the total number of microorganisms. When storing seeds from 2018 in order to reduce the number of yeasts and moulds, a slightly lower number was spotted when seeds were stored in a vacuum-sealed bag, at the refrigerator / freezer temperature. For hemp seeds produced in 2019, the most optimal storage conditions were at the refrigerator (for reduction of Enterobacteriaceae) and freezer temperature (for reduction of the total number of microorganisms). For the reduction of the total number of moulds and yeasts, optimal conditions were at room temperature. Ethanol (75%, v/v) was the most effective disinfectant among the tested chemicals regardless of the initial load of microorganisms, with log reduction of 3.2 (for Enterobacteriaceae), 2.9 log (for the total number of microorganisms), and total reduction of yeasts and moulds after 10 minutes, for the seeds harvested in 2019, which were far more contaminated than the seeds harvested in 2018. Considering the price of the disinfection method with ethanol, sodium hypochlorite may be a better solution for the reduction of the microbial number on the seeds.